Specificities of Communication in Children with Intellectual Disorders - Zashchirinskaia, Oksana V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of this work is to study the characteristics of communication in children with intellectual disabilities. Background: The study of the specificities of communication in children with intellectual disabilities has become more and more relevant in the past few years. Method: The methodological basis of this study was the combination of various theoretical methods of cognition. Results: In the process of writing this work, the author studied the techniques of verbal and non-verbal communication. The works of Russian and foreign authors, as well as methods of improving communication in children with intellectual disabilities, were considered. It was found that the impact of intellectual disabilities with mild mental retardation on the cognitive, behavioural and emotional-personal spheres of the communicative process naturally entails the emergence of serious difficulties in establishing contacts with people around, and therefore in the process of social adaptation of the child in general. Conclusion: The practical significance of this work lies in the study of the characteristics of communication in children with intellectual disabilities, which will be useful for psychologists, teachers and medical workers. The study and research of this topic will provide further opportunities for the development of a program of psychological influence to optimise communication for children with intellectual disabilities and their adaptation in society.